Blackleg In Cattle - Max B. Irsik (EDIS)
VM-165, a 2-page fact sheet by M.B. Irsik, DVM, MAB, describes this highly fatal disease of skeletal and heart muscles in cattle, the infective agent, the disease process, clinical signs, treatment, and prevention. Published by the UF Department of Veterinary Medicine -- Large Animal Clinical Sciences, March 2007.